Diseminasi Teknologi Mesin Peniris Minyak di Kelurahan Pelintung, Kota Dumai - Bobby Demeianto; Rizqi Ilmal Yaqin; Hafiz Ziddin; Juniawan Preston Siahaan; Iskandar Musa; Mula Tumpu; Yuniar Endri Priharanto; Muhammad Nur Arkham (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Fisheries products from marine sector really need to be considered because Indonesia, especially in the waters of Dumai City, has abundant fish resources of up to 571 tons/year. Diversification of processed fish is a solution so that processed fish can be consumed by the community. On the other hand, the local community of Pelintung Village, Dumai City, still lacks appropriate technology that can improve the quality of processed products from diversification. Some processed fish products are of poor quality. Community service activities aim to provide knowledge transfer and use of oil draining machines so that people can improve the quality of processed fish or non-fish. This community service activity uses the method of applying the use of an oil draining machine in Pelintung Village. The essence of this event is the delivery of theoretical and practical material about oil draining machines. The pre-test was carried out before the material was delivered and the post-test was carried out after the material was delivered. Filling in the satisfaction index is done along with filling out the post-test. The results of this activity stated that the community was very enthusiastic as the percentage of correct answers for the pre-test and post-test increased. The results of the pre-test and post-test in the knowledge, operation and maintenance categories increased to 75%, 84% and 100%, respectively. The satisfaction level of participants was also stated to be satisfied with the percentage of 61.7% and getting benefits from this community service activity. This activity must continue to be evaluated so that when holding similar activities, it can be more effective, efficient and sustainable. Recommendations for service activities in the form of processing fishery products that can be practiced directly with the community will be better in the future.